Electroheliuminescent platform for solid phase determination of polycyclic aromatic hydrocarbons at ultra-trace level - Khaled, G.; Kukoba, A.; Bilash, O.; Zoludov, Yu.; Snizhko, D.; Muzyka, K. (Radiotekhnika, 2018)
An electrochemiluminescent (ECL) platform is proposed to determine the trace concentrations of polycyclic aromatic hydrocarbons (PAH) in water. Due to the PAH extraction from the aqueous solution, followed by transfer to Langmuir-Blodgett films, their immobilization on the electrode and the solid-state ECL detection has opened the possibility of determining the surfactant level at trace concentrations in the linear range 10-10 ÷ 10-13 mol.